(untitled) (World Economics and Finance Bulletin, 2024)
This article export of agricultural products plays a very important role in the development of the economy of our republic. Improving the system of export of agricultural products, in turn, requires its specific aspects. To date, many measures are being taken in this regard in the development of the sector